العلاقات العامة السّياحيّة.. الطريق نحو تحقيق التّنميّة السّياحيّة المستدامة - محمودي, محمد بشير (جامعة الوادي - University of Eloued, 2022)
إنّ الحديث عن العلاقات العامة السّياحيّة يجُرّنا للحديث عن السّياحة المستدامة الذّي يعتبرها الكثيرون مُجرّد أماكن أثرّية ومواقع تاريخيّة، وماهي في حقيقة الأمر تُعد هويّة المكان أو المنطقة التّي تُعتبر جُزءًا من ذلك البلد. لذا فالسّياحة تُعد بمثابة هويّة بلد أو مجتمع يهتم بحماية التّراث الثقافي للمقاصد السّياحيّة، والاستغلال الأمثل للموارد الطّبيعية والسّياحيّة والثّقافيّة الـمُتاحة دُون استنزافها، إضافة لحماية الثّقافات المحليّة وخصائصها البيئية والثّقافية والاجتماعيّة. في المقابل تعد العلاقات العامة في مجال السّياحة وحدة تتكون من أجزاء وأنظمة فرعيّة تتداخل وتتبادل العلاقات فيما بينها وتعتمد كل منها على الآخر بشكل متكامل لتحقيق أهداف النظام السّياحي الذي يشمل العديد من الأنظمة الفرعيّة كالخدمات، السّياح، المنشآت السّياحيّة، الاجهزة الرّسمية والبيئة الخارجيّة. Talking about tourism public relations leads us to talk about sustainable tourism, which many consider to be mere archaeological places and historical sites, and what in fact is the identity of the place or region that is part of that country. Therefore, tourism is considered as the identity of a country or society concerned with protecting the cultural heritage for tourist destinations, and making optimal use of the available natural, tourism and cultural resources without depleting them, in addition to protecting local cultures and their environmental, cultural and social characteristics. On the other hand, public relations in the field of tourism is a unit consisting of parts and sub-systems that overlap and exchange relations among themselves and depend on each other in an integrated manner to achieve the objectives of the tourism system, which includes many sub-systems such as services, tourists, tourist facilities, official agencies and the external environment.
مقال
Keywords: العلاقات العامة- العلاقات العامة السياحية-التنمية-السياحة المستدامة; Public relations; tourism public relations; development; sustainable tourism